Gram-negative folliculitis. A rare problem or is it underdiagnosed? Case report and literature review - Sierra-Téllez Daniela; Ponce-Olivera Rosa María; Tirado-Sánchez Andrés; Hernández Marco Antonio; Bonifaz Alexandro (Our Dermatology Online, 2011)
AbstractGram-negative folliculitis may be the result of prolonged antibacterial treatments in patients with acne and rosacea. It is caused by alteration of facial skin flora and the nasal mucous, a decrease of Gram-positive bacteria and a proliferation of Gram-negative bacteria (for example Escherichia coli, Pseudomonas aeruginosa, Serratia marcescens, Klebsiella sp. and Proteus mirabilis). It should be considered in patients with acne who have not had a clinical improvement after 3-6 months of treatment with tetracyclines. The disease is underestimated, probably because bacteriological studies are rarely requested and the increased use of oral isotretinoin for acne management. One of the most effective treatments for Gram-negative folliculitis is oral isotretinoin (0.5-1 mg / kg / day for 4-5 months). We report the case of Gram negative folliculitis successfully treated with oral isotretinoin.